PENGARUH PEMAHAMAN PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DIMODERASI SOSIALISASI PERPAJAKAN - Dymas Setiawan (2022)
In creating successful taxation, an active role for taxpayers is needed to comply with their tax obligations. This study aims to determine whether there is an influence from taxation understanding and taxpayer awareness on individual taxpayer compliance moderate by taxation socialization. This study uses a quantitative method with the population being individual taxpayers who are registered at Jakarta Pasar Minggu Pratama Tax Service Office. The sampling technique used is simple random sampling with a total sample of 116 respondents. The data was processed and tested using the Partial Least Square method with the SmartPLS 3.0 application. The results of this study indicate that the understanding of taxation and awareness of taxpayer had a positive effect on individual taxpayer compliance. Meanwhile, tax socialization cannot strengthen the influence of tax understanding and taxpayer awareness on individual taxpayer compliance.